Negative electrode for rechargeable lithium battery and rechargeable lithium battery including same
Patent Information
- Application Number
- KR1020210116513
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-01
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2041-09-01
Smart Images

Figure 112021101401262-PAT00018_ABST
Abstract
Description
Technology Field
[0001] The invention relates to a negative electrode for a lithium secondary battery and a lithium secondary battery including the same. Background Technology
[0002] With the recent rapid proliferation of battery-powered electronic devices such as mobile phones, laptop computers, and electric vehicles, the demand for rechargeable batteries that are small, lightweight, and relatively high-capacity is increasing rapidly. In particular, lithium-ion batteries are gaining popularity as power sources for portable devices due to their lightweight nature and high energy density.
[0003] A lithium secondary battery is a battery comprising a positive electrode and a negative electrode containing an active material capable of intercalating and deintercalating lithium ions, and an electrolyte, and produces electrical energy through oxidation and reduction reactions when lithium ions are intercalated and deintercalated at the positive electrode and the negative electrode.
[0004] Transition metal compounds such as lithium cobalt oxide, lithium nickel oxide, and lithium manganese oxide are primarily used as positive electrode active materials for lithium secondary batteries. Crystalline carbon materials, such as natural graphite or synthetic graphite, or amorphous carbon materials are used as negative electrode active materials. The problem to be solved
[0005] One embodiment provides a negative electrode for a lithium secondary battery exhibiting high energy density and excellent cycle life characteristics.
[0006] Another embodiment provides a lithium secondary battery comprising the above-mentioned negative electrode. means of solving the problem
[0007] One embodiment provides a negative electrode for a lithium secondary battery comprising a current collector and a negative electrode active material layer located on the current collector, wherein the negative electrode active material layer comprises a silicon-based negative electrode active material, a room temperature molten salt, and a volume expansion reducing binder.
[0008] The volume expansion reducing binder may be a copolymer comprising units derived from poly(meth)acrylic acid monomers and units derived from (meth)acrylonitrile monomers, polyvinyl alcohol, polyacrylic acid, polyacrylonitrile, polyvinylidene fluoride, or a combination thereof. In one embodiment, the volume expansion reducing binder may be polyvinyl alcohol, polyacrylic acid, or a combination thereof.
[0009] In one embodiment, the volume expansion reducing binder may include a first copolymer comprising a unit derived from a poly(meth)acrylic acid monomer and a unit derived from a (meth)acrylonitrile monomer, and may also include a second copolymer comprising a unit derived from an ethylenically unsaturated monomer that is at least one of an unsaturated carboxylic acid alkyl ester monomer, a (meth)acrylic acid monomer, and an unsaturated carboxylic acid amide monomer, and a unit derived from an aromatic vinyl monomer.
[0010] The above room temperature molten salt may include a cation that is any one of the cations represented by the following chemical formulas 1 to 5.
[0011] [Chemical Formula 1]
[0012]
[0013] (In the above chemical formula 1,
[0014] R 1 , R 2 , R 3 and R 4 The groups are identical or different from each other and are hydrogen, unsubstituted or substituted aliphatic groups, unsubstituted or substituted aromatic groups, unsubstituted or substituted heterocyclic groups, or unsubstituted or substituted alkoxy groups.
[0015] [Chemical Formula 2]
[0016]
[0017] (In the above chemical formula 2,
[0018] R 5is an alkyl group of 1-5 hydrogen atoms or carbon atoms, and
[0019] R 6 , R 7 , R 8 The groups are identical or different from each other, and are hydrogen, a C1-C5 alkyl group, an alkoxy group, an amino group, or a nitro group, and
[0020] m is 4 or 5.)
[0021] [Chemical Formula 3]
[0022]
[0023] (In the above chemical formula 3,
[0024] R 9 is an alkyl group of 1-5 hydrogen atoms or carbon atoms, and
[0025] R 10 , R 11 , R 12 The groups are identical or different from each other, and are hydrogen, a C1-C5 alkyl group, an alkoxy group, an amino group, or a nitro group, and
[0026] m1 is 4 or 5)
[0027] [Chemical Formula 4]
[0028]
[0029] (In the above chemical formula 4,
[0030] R 13 It is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and
[0031] R 14 , R 15 , R 16 The groups are identical or different from each other, and are hydrogen, a C1-C5 alkyl group, an alkoxy group, an amino group, or a nitro group, and
[0032] R 17 is an alkyl group having 1 to 5 carbon atoms, and
[0033] m2 is an integer from 0 to 2, and m+n is 3 or 4.
[0034] [Chemical Formula 5]
[0035]
[0036] (In the above chemical formula 5,
[0037] R 18 It is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and
[0038] R 19 , R 20 , R 21 The groups are identical or different from each other, and are hydrogen, a C1-C5 alkyl group, an alkoxy group, an amino group, or a nitro group, and
[0039] R 22 is an alkyl group having 1 to 5 carbon atoms, and
[0040] m2 is an integer from 0 to 2, and m+n is 3 or 4.
[0041] In one embodiment, the cation may be an alkyl quaternary ammonium cation, an N-methyl-N-propylpiperidinium cation, or an N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium cation.
[0042] The above room temperature molten salt may include an anion having a fluorine atom. The above anion having a fluorine atom is BF4 - , PF6 - , C n F 2n+1 CO2 - (n is an integer from 1 to 4), C m F 2m+1 SO3 - (m is an integer from 1 to 4), (FSO2)2N - , (CF3SO2)2N - , (C2F5SO2)2N - , (CF3SO2)(C4F9SO2)N - , (CF3SO2)3C - , CF3SO2-N - -COCF3 or R a -SO2-N - -SO2CF3(R aIt may represent an aliphatic or aromatic group.
[0043] The content of the above room temperature molten salt may be 0.1% to 5% by weight with respect to 100% by weight of the entire cathode active material layer.
[0044] The content of the volume expansion reducing binder may be 2% to 6% by weight with respect to 100% by weight of the entire cathode active material layer.
[0045] The weight ratio of the above room temperature molten salt and the above volume expansion reducing binder may be 0.3 to 1:3.
[0046] The above silicon-based negative electrode active material is Si, SiO x (0 < x < 2), Si-Q alloy (wherein Q is an element selected from the group consisting of alkali metals, alkaline earth metals, group 13 elements, group 14 elements, group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof, and is not Si), Si-carbon complex, or a combination thereof.
[0047] According to another embodiment, a lithium secondary battery comprising the above-mentioned cathode, a positive electrode, and an electrolyte is provided. Effects of the invention
[0048] The cathode active material according to one embodiment can exhibit high energy density and excellent cycle life characteristics. Brief explanation of the drawing
[0049] FIG. 1 is a schematic diagram showing the structure of a negative electrode for a lithium secondary battery according to one embodiment. Specific details for implementing the invention
[0050] Hereinafter, embodiments of the present invention will be described in detail. However, these are presented as examples and are not intended to limit the present invention, and the present invention is defined only by the scope of the claims set forth below.
[0051] A negative electrode for a lithium secondary battery according to one embodiment comprises a current collector and a negative electrode active material layer located on the current collector, and the negative electrode active material layer may comprise a silicon-based negative electrode active material, a room temperature molten salt, and a volume expansion reducing binder.
[0052] The above room temperature molten salt may include a cation that is any one of the cations represented by the following chemical formulas 1 to 5.
[0053] [Chemical Formula 1]
[0054]
[0055] In the above chemical formula 1,
[0056] R 1 , R 2 , R 3 R4 and R4 are identical or different from each other and are hydrogen, an unsubstituted or substituted aliphatic group, an aromatic group, a heterocyclic group, or an unsubstituted or substituted alkoxy group. The aliphatic group may be, for example, an alkyl group, an alkoxyl group, or an alkenyl group, and the alkyl group may be an alkyl group having 1 to 8 carbon atoms, for example, a methyl group, an ethyl group, a propyl group, a hexyl group, an octyl group, etc. In addition, the substituted aliphatic group may be, for example, a methoxyalkyl group.
[0057] The functional group of the "substituted" mentioned above may be, for example, a hydrocarbon group having 1 to 10 carbon atoms, a hydroxyalkyl group, or an alkoxyalkyl group.
[0058] Examples of the above aromatic groups include aryl groups. Examples of the above heterocyclic groups include pyrrole, pyridine, imidazole, pyrazol, benzimidazole, piperidine, pyrrolidine, carbazole, quinoline, pyrrolidinium, piperidinium, piperadinium, etc.
[0059] [Chemical Formula 2]
[0060]
[0061] In the above chemical formula 2,
[0062] R5 is an alkyl group of 1-5 hydrogen atoms or carbon atoms, and
[0063] R 6 , R 7 , R 8 The groups are identical or different from each other, and are hydrogen, a C1-C5 alkyl group, an alkoxy group, an amino group, or a nitro group, and
[0064] m is 4 or 5.
[0065] [Chemical Formula 3]
[0066]
[0067] (In the above chemical formula 3,
[0068] R 9 is an alkyl group of 1-5 hydrogen atoms or carbon atoms, and
[0069] R 10 , R 11 , R 12 The groups are identical or different from each other, and are hydrogen, a C1-C5 alkyl group, an alkoxy group, an amino group, or a nitro group, and
[0070] m1 is 4 or 5)
[0071] [Chemical Formula 4]
[0072]
[0073] (In the above chemical formula 4,
[0074] R 13 It is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and
[0075] R 14 , R 15 , R 16 The groups are identical or different from each other, and are hydrogen, a C1-C5 alkyl group, an alkoxy group, an amino group, or a nitro group, and
[0076] R 17 is an alkyl group having 1 to 5 carbon atoms, and
[0077] m2 is an integer from 0 to 2, and m+n is 3 or 4.
[0078] [Chemical Formula 5]
[0079]
[0080] (In the above chemical formula 5,
[0081] R 18 It is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and
[0082] R 19 , R 20 , R 21 The groups are identical or different from each other, and are hydrogen, a C1-C5 alkyl group, an alkoxy group, an amino group, or a nitro group, and
[0083] R 22 is an alkyl group having 1 to 5 carbon atoms, and
[0084] m2 is an integer from 0 to 2, and m+n is 3 or 4.
[0085] Chemical formulas 2 and 4 represent structures having conjugate bonds, and chemical formulas 3 and 5 represent structures not having conjugate bonds.
[0086] In one embodiment, the cation may be a cation of Formula 1 or a cation of Formula 3.
[0087] The cation of Chemical Formula 1 above may be, for example, an alkyl quaternary ammonium cation. In Chemical Formula 1, the alkyl quaternary ammonium cation is R 1 to R 3 This is a methyl group, and R 4 α can be an alkyl group or an alkenyl group having 3 to 8 carbon atoms.
[0088] Examples of the cations of Formula 1 according to one embodiment include alkyl quaternary cations such as trimethylpropylammonium cation, trimethyloctylammonium cation, trimethylarylammonium cation, and trimethylhexylammonium cation, and N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium cation.
[0089] The cations of the above chemical formulas 2 to 5 may be, for example, pyrrolium cation, pyridinium cation, imidazolium cation, pyrazolium cation, benzimidazolium cation, indolium cation, carbazolium cation, quinolinium cation, pyrrolidinium cation, piperidinium cation, piperazinium cation, or a combination thereof, and some of the functional groups of these may be substituted with a hydrocarbon group having 1 to 10 carbon atoms, a hydroxyalkyl group, or an alkoxyalkyl group. Specific examples include ethylmethylimidazolium cation and N-methyl-N-propylpiperidinium cation.
[0090] The above room temperature molten salt may include an anion having a fluorine atom. The above anion having a fluorine atom is BF4 - , PF6 - , C n F 2n+1 CO2 - (n is an integer from 1 to 4), C m F 2m+1 SO3 - (m is an integer from 1 to 4), (FSO2)2N - , (CF3SO2)2N - , (C2F5SO2)2N - , (CF3SO2)(C4F9SO2)N - , (CF3SO2)3C - , CF3SO2-N - -COCF3 or R a -SO2-N - -SO2CF3(R a (representing an aliphatic or aromatic group) may be an example. According to one embodiment, the anion having the fluorine atom is BF4 - , (FSO2)2N - , (C2F5SO2)2N - or CF3SO2)(C4F9SO2)N - It may be, and according to other implementation examples, BF4 - , (FSO2)2N - or (CF3SO2)2N -It could be.
[0091] The above aliphatic group and the above aromatic group are identical to the definitions described above.
[0092] In one embodiment, the room temperature molten salt may comprise the alkyl quaternary ammonium cation and an anion having a fluorine atom, for example, the alkyl quaternary ammonium cation is R 1 to R 3 ga is a methyl group, and R 4 Formula 1, in which is an alkyl or alkenyl group having 3 to 8 carbon atoms, and the anion having a fluorine atom is (CF3SO2)2N - , (C2F5SO2)2N - or (CF3SO2)(C4F9SO2)N - It can be a room temperature molten salt.
[0093] Examples of room temperature molten salts according to one embodiment include trimethylpropylammonium bis(trifluoromethylsulfonyl)imide, trimethyloctylammonium bis(trifluoromethylsulfonyl)imide, trimethylarylammonium bis(trifluoromethylsulfonyl)imide, trimethylhexylammonium bis(trimethylfluorosulfonyl)imide, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethylsulfonyl)imide (hereinafter referred to as "DEMETFSI"), N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium tetrafluoroborate (hereinafter referred to as "DEMEBF4"), etc.
[0094] Examples of room temperature molten salts containing cations of the above chemical formulas 2 to 5 and anions having fluorine atoms include 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (hereinafter referred to as "EMITFSI"), 1-ethyl-3-methylimidazolium tetrafluoroborate (hereinafter referred to as "EMIBF4"), N-methyl-N-propylpiperidinium bis(trifluoromethylsulfonyl)imide (hereinafter referred to as "PP13TFSI"), and N-methyl-N-propylpiperidinium bis(fluorosulfonyl)imide (hereinafter referred to as "PP13FSI").
[0095] As room temperature molten salt is incorporated into the negative electrode active material layer, flexibility can be imparted during electrode manufacturing, thereby effectively suppressing crack formation. Since the room temperature molten salt has zero vapor pressure and is incorporated into the binder in a liquid state during the electrode drying process, it can be included within the polymer matrix of a volume expansion-reducing binder, which may exist in the form of a polymer matrix, thereby causing the binder to soften. Consequently, sufficient flexibility can be imparted to the negative electrode. Furthermore, process defects caused by the detachment of the active material layer during the manufacturing process, as well as short circuits within the battery and non-uniformity of battery reactions caused by detached materials, can be suppressed.
[0096] In one embodiment, the content of the room temperature molten salt may be 0.1% to 5% by weight, 0.1% to 1% by weight, or 0.3% to 1% by weight with respect to 100% by weight of the entire cathode active material layer. When the content of the room temperature molten salt falls within the above range, it may exhibit the advantage of having a binder composition with sufficiently high ionic conductivity.
[0097] However, even if the above-mentioned room temperature molten salt is used, if a binder having sufficient swelling characteristics that can be combined with the room temperature molten salt is not used together, the effect of preventing electrode cracking due to the use of the room temperature molten salt cannot be obtained.
[0098] The above volume expansion reducing binder may be a copolymer comprising units derived from poly(meth)acrylic acid monomers and units derived from (meth)acrylonitrile monomers, polyvinyl alcohol, polyacrylic acid, polyacrylonitrile, polyvinylidene fluoride, or a combination thereof.
[0099] In one embodiment, the volume expansion reducing binder may be polyvinyl alcohol, polyacrylic acid, or a combination thereof.
[0100] The volume expansion reducing binder may be 2% to 6% by weight, 2% to 5% by weight, or 3% to 5% by weight based on 100% by weight of the entire cathode active material layer. When the volume expansion reducing binder content falls within the above range, high binding strength, volume expansion reduction effect, and sufficient low resistance characteristics can be obtained.
[0101] In one embodiment, the preferred weight ratio of the room temperature molten salt and the volume expansion reducing binder may be 0.3 to 1:3. When the weight ratio of the room temperature molten salt and the binder falls within the above range, the room temperature molten salt can ideally be contained within the binder and can have high ionic conductivity and sufficient strength.
[0102] Although silicon-based negative electrode active materials have a problem of severe volume expansion during charging and discharging, the volume expansion reducing binder enables the silicon-based negative electrode active materials to firmly adhere to each other and to adhere well to the current collector, thereby effectively suppressing volume expansion. Furthermore, since volume expansion can be effectively suppressed, cycle life characteristics can be improved as a result.
[0103] Since carbon-based negative electrode active materials undergo almost no volume expansion, even if the volume expansion-reducing binder is used, the effect of suppressing volume expansion is negligible, and consequently, the effect of improving cycle life characteristics is also negligible. Furthermore, when the volume expansion-reducing binder is used with carbon-based negative electrode active materials, it may actually increase the resistance of the electrode and inhibit the reaction on the surface of the active material within the electrode.
[0104] In addition, even when the above volume expansion reduction binder is used in the anode, the effect of improving cycle life characteristics may be negligible, similar to when it is applied to a carbon-based cathode active material.
[0105] In particular, the effect of improving energy density and cycle life characteristics is obtained when a room-temperature molten salt and a volume expansion-reducing binder are used together with a silicon-based anode active material, and cannot be obtained when only one of them is used. Furthermore, as explained above, the effect obtained by using a room-temperature molten salt and a volume expansion-reducing binder together is obtained when used with a silicon-based anode active material; if used with a carbon-based anode active material or anode active material, it cannot be obtained because it increases electrode resistance and inhibits reactions on the surface of the active material within the electrode.
[0106] When a copolymer is used as a volume expansion reducing binder, the first copolymer may comprise a copolymer comprising a unit derived from a poly(meth)acrylic acid monomer and a unit derived from a (meth)acrylonitrile monomer, and the second copolymer may comprise a unit derived from an ethylenically unsaturated monomer that is at least one of an unsaturated carboxylic acid alkyl ester monomer, a (meth)acrylic acid monomer, and an unsaturated carboxylic acid amide monomer, and a unit derived from an aromatic vinyl monomer.
[0107] In the first copolymer above, the content of the (meth)acrylic acid-based monomer-derived unit is 35% to 65% by weight, and the content of the (meth)acrylonitrile-derived unit may be 35% to 65% by weight.
[0108] In the first copolymer above, when the content of the unit derived from the (meth)acrylic acid-based monomer is included within the above range, it is suitable for having appropriate water solubility, further improving the dispersibility of the negative electrode active material, improving the storage safety of the composition for manufacturing the negative electrode, and effectively suppressing crack occurrence during negative electrode manufacturing.
[0109] The above (meth)acrylic acid-based monomer may be at least one of (meth)acrylic acid, an alkali metal salt of (meth)acrylic acid, and an ammonium salt of (meth)acrylic acid. Meanwhile, the above (meth)acrylic acid refers to acrylic acid or methacrylic acid. Examples of the above alkali metal salt of (meth)acrylic acid include sodium acrylate, lithium acrylate, potassium acrylate, calcium acrylate, magnesium acrylate, sodium methacrylate, lithium methacrylate, potassium methacrylate, calcium methacrylate, etc., and according to one embodiment, it may be sodium acrylate. Examples of the above ammonium salt of (meth)acrylic acid include ammonia neutralized product of (meth)acrylic acid, monoethanolamine neutralized product, diethanolamine neutralized product, hydroxylamine neutralized product, etc., and according to one embodiment, it may be an ammonia neutralized product of acrylic acid.
[0110] In addition, it may contain a third monomer-derived unit copolymerizable with a (meth)acrylic acid-based monomer and / or a (meth)acrylonitrile monomer, and the content of the third monomer-derived unit may be greater than 0 parts by weight and less than or equal to 20 parts by weight with respect to 100 parts by weight of the total copolymer.
[0111] The above third monomer may include a hydroxyl group-containing monomer or an amide group-containing monomer. Examples of the above hydroxyl group-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyhexyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, (4-hydroxymethylcyclohexyl)methylacrylate, N-methylol (meth)acrylamide, N-hydroxy(meth)acrylamide, vinyl alcohol, allyl alcohol, 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, diethylene glycol monovinyl ether, etc. Examples of monomers containing the above amide group include acrylamide, methacrylamide, diethyl(meth)acrylamide, N-vinylpyrrolidone, N-vinyl-2-pyrrolidone, N-(meth)acryloylpyrrolidone, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylacrylamide, N,N-diethylmethacrylamide, N,N'-methylenebisacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethacrylamide, etc.
[0112] When the second copolymer is further included, the content ratio of the first copolymer and the second copolymer may be 50 to 95 parts by weight or 60 to 90 parts by weight of the first copolymer with respect to 100 parts by weight of the second copolymer.
[0113] When the content of the first copolymer is included in the above range, the strength and elasticity modulus of the binder are further improved, the electrode expansion of the negative electrode can be suppressed more effectively, the flexibility of the binder is improved, and cracks are hardly generated during the coating and drying process of the negative electrode slurry, making it easy to manufacture the electrode and improving the cycle characteristics of the secondary battery containing it.
[0114] Examples of aromatic vinyl monomers include styrene, α-methylstyrene, methoxystyrene, trifluoromethylstyrene, divinylbenzene, etc., and according to one embodiment, it may be styrene.
[0115] The ethylenically unsaturated monomer may be at least one of an unsaturated carboxylic acid alkyl ester monomer, a (meth)acrylic acid-based monomer, and an unsaturated carboxylic acid amide monomer.
[0116] Examples of unsaturated carboxylic acid alkyl ester monomers include (meth)acrylate 2-ethylhexyl, (meth)acrylate methyl, (meth)acrylate ethyl, (meth)acrylate n-butyl, (meth)acrylate tert-butyl, (meth)acrylate cyclohexyl, (meth)acrylate lauryl, (meth)acrylate benzyl, (meth)acrylate isobornyl, (meth)acrylate 2-hydroxyethyl, (meth)acrylate 2-hydroxypropyl, (meth)acrylate 4-hydroxybutyl, (meth)acrylate glycidyl, etc.
[0117] Examples of (meth)acrylic acid-based monomers include (meth)acrylic acid, maleic acid, fumaric acid, itaconic acid, etc.
[0118] Examples of unsaturated carboxylic acid amide monomers include (meth)acrylamide, isopropylacrylamide, N-methylol acrylamide, N-hydroxyethylacrylamide, N-hydroxybutylacrylamide, dimethylacrylamide, diethylacrylamide, etc.
[0119] In the second copolymer, the content of the unit derived from the ethylene fluorinated monomer may be 5 weight% or more with respect to 100 weight% of the second copolymer. When the content of the unit derived from the ethylene unsaturated monomer is 5 weight% or more with respect to 100 weight% of the second copolymer, the flexibility of the binder is improved, cracks do not occur during the coating and drying process of the cathode slurry, making it easy to manufacture the electrode, and the adhesion of the cathode composite layer to the substrate is improved, so that a battery with excellent cycle characteristics can be obtained.
[0120] The above silicon-based negative electrode active material is Si, SiO x (0 < x < 2), Si-Q alloy (wherein Q is an element selected from the group consisting of alkali metals, alkaline earth metals, group 13 elements, group 14 elements, group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof, and is not Si), Si-carbon complex, or a combination thereof.
[0121] The above Si-carbon composite may include silicon and crystalline carbon. In this case, the average particle diameter (D50) of the silicon particles may be 10 nm to 200 nm. The above Si-carbon composite may further include an amorphous carbon layer formed in at least a portion. Unless otherwise defined in this specification, the average particle diameter (D50) refers to the diameter of a particle in which the cumulative volume in the particle size distribution is 50 volume%. The silicon content in the above Si-carbon composite may be 1 to 60 weight%.
[0122] The average particle size (D50) can be measured using methods widely known to those skilled in the art, for example, by using a particle size analyzer, or by using transmission electron microscope (TEM) images or scanning electron microscope (SEM) images. Alternatively, the average particle size (D50) value can be obtained by using a measuring device utilizing dynamic light scattering, performing data analysis to count the number of particles for each particle size range, and then calculating from this.
[0123] The negative electrode active material may include the silicon-based negative electrode active material as the first negative electrode active material and the carbon-based negative electrode active material as the second negative electrode active material. In this case, the mixing ratio of the first negative electrode active material and the second negative electrode active material may be included in a weight ratio of 1:99 to 50:50. More specifically, the negative electrode active material may include the first negative electrode active material and the second negative electrode active material in a weight ratio of 5:95 to 20:80.
[0124] The above carbon-based cathode active material may be crystalline carbon, and this crystalline carbon may be artificial graphite, natural graphite, or a combination thereof.
[0125] The content of the above-mentioned negative electrode active material may be 90% to 98% by weight and 92% to 97% by weight with respect to 100% by weight of the entire negative electrode active material layer.
[0126] The above negative electrode active material layer may further include a conductive material. When the negative electrode active material layer further includes a binder, the negative electrode active material layer may include 85% to 97.9% by weight of negative electrode active material, 0.1% to 5% by weight of room temperature molten salt, 1% to 5% by weight of binder, and 1% to 5% by weight of conductive material.
[0127] The above conductive material is used to impart conductivity to the electrode, and any electronically conductive material that does not cause chemical changes can be used in the battery being constructed. Examples of conductive materials may include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, and carbon fibers; metal-based materials such as metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; or conductive materials comprising mixtures thereof.
[0128] As the above current collector, a material selected from the group consisting of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof may be used.
[0129] Another embodiment provides a lithium secondary battery comprising the above-mentioned cathode, a positive electrode, and an electrolyte.
[0130] The above anode includes a current collector and an anode active material layer formed on the current collector.
[0131] As the above-mentioned cathode active material, a compound capable of reversible intercalation and deintercalation of lithium (a rethated intercalation compound) may be used. Specifically, one or more composite oxides of lithium and a metal selected from cobalt, manganese, nickel, and combinations thereof may be used. As a more specific example, a compound represented by any one of the following chemical formulas may be used. Li a A 1-b X b D2(0.90 ≤ a ≤1.8, 0 ≤ b ≤ 0.5); Li a A 1-b X b O 2-c D c (0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05); Li a E 1-b Xb O 2-c D c (0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05); Li a HAVE BEEN 2-b X b O 4-c D c (0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05); Li a Ni 1-b-c Co b X c D α (0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.5, 0 < α ≤ 2); Li a Ni 1-b-c Co b X c O 2-α T α (0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤0.05, 0 < α < 2); Li a Ni 1-b-c Co b X c O 2-α T2(0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤0.05, 0 < α < 2); Li a Ni 1-b-c Mr b X c D α (0.90 ≤a ≤1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α ≤ 2); Li a Ni 1-b-c Mr b X c O 2-α T α (0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α < 2); Li a Ni 1-b-c Mr b X c O 2-αT2(0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α < 2); The a Nor b E c G d O2(0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.9, 0 ≤ c ≤0.5, 0.001 ≤ d ≤ 0.1); The a Nor b Co c Mn d G e O2(0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.9, 0 ≤ c ≤ 0.5, 0 ≤ d ≤ 0.5, 0 ≤ e ≤ 0.1); The a Nor b Co c Al d G e O2(0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.9, 0 ≤ c ≤ 0.5, 0 ≤ d ≤ 0.5, 0 ≤ e ≤ 0.1); The a Nor b Co c Mn d G e O2(0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.9, 0 ≤ c ≤ 0.5, 0 ≤ d ≤ 0.5, 0.001 ≤ e ≤0.1);Li; a NiG b O2(0.90 ≤ a ≤ 1.8, 0.001 ≤ b ≤ 0.1); The a CoG b O2(0.90 ≤ a ≤ 1.8, 0.001 ≤ b ≤ 0.1); The a Mn 1-b G b O2(0.90 ≤ a ≤ 1.8, 0.001 ≤ b ≤0.1);Li a Mn2G b O4(0.90 ≤ a ≤1.8, 0.001 ≤ b ≤ 0.1); The a Mn 1-g G gPO4(0.90 ≤ a ≤ 1.8, 0 ≤ g ≤ 0.5); QO2; QS2; LiQS2; V2O5; LiV2O5; LiZO2; LiNiVO4Li (3-f) J2(PO4)3(0 ≤f ≤2); Li (3-f) Fe2(PO4)3(0 ≤ f ≤ 2); Li a FePO4(0.90 ≤ a ≤ 1.8)
[0132] In the above chemical formula, A is selected from the group consisting of Ni, Co, Mn, and combinations thereof; X is selected from the group consisting of Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements, and combinations thereof; D is selected from the group consisting of O, F, S, P, and combinations thereof; E is selected from the group consisting of Co, Mn, and combinations thereof; T is selected from the group consisting of F, S, P, and combinations thereof; G is selected from the group consisting of Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, and combinations thereof; Q is selected from the group consisting of Ti, Mo, Mn, and combinations thereof; Z is selected from the group consisting of Cr, V, Fe, Sc, Y, and combinations thereof; and J is selected from the group consisting of V, Cr, Mn, Co, Ni, Cu, and combinations thereof.
[0133] Of course, a coating layer on the surface of this compound may be used, or a mixture of the compound and a compound having a coating layer may be used. This coating layer may include at least one coating element compound selected from the group consisting of oxides of coating elements, hydroxides of coating elements, oxyhydroxides of coating elements, oxycarbonates of coating elements, and hydroxycarbonates of coating elements. The compounds forming these coating layers may be amorphous or crystalline. As coating elements included in the coating layer, Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or mixtures thereof may be used. For the coating layer formation process, any coating method may be used as long as the compound can be coated using these elements in a way that does not adversely affect the physical properties of the cathode active material (e.g., spray coating, immersion method, etc.). Since this is a matter that is well understood by those skilled in the art, a detailed explanation will be omitted.
[0134] In the above anode, the content of the anode active material may be 90% to 98% by weight with respect to the total weight of the anode active material layer.
[0135] In one embodiment, the positive active material layer may further include a binder and a conductive material. In this case, the content of the binder and the conductive material may each be 1% to 5% by weight with respect to the total weight of the positive active material layer.
[0136] The above binder serves to adhere the positive active material particles well to each other and also to adhere the positive active material well to the current collector. Representative examples of binders include polyvinyl alcohol, carboxymethylcellulose, hydroxypropylcellulose, diacetylcellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc., but are not limited thereto.
[0137] The above conductive material is used to impart conductivity to the electrode, and any electronically conductive material that does not cause chemical changes can be used in the battery being constructed. Examples of conductive materials include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, and carbon fibers; metal-based materials such as metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; or conductive materials comprising mixtures thereof.
[0138] Al may be used as the current collector mentioned above, but is not limited thereto.
[0139] The above electrolyte includes a non-aqueous organic solvent and a lithium salt.
[0140] The above-mentioned non-aqueous organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can move.
[0141] The above-mentioned non-aqueous organic solvent may be a carbonate-based, ester-based, ether-based, ketone-based, alcohol-based, or aprotic solvent.
[0142] The above carbonate-based solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. The above ester-based solvents may include methyl acetate, ethyl acetate, n-propyl acetate, t-butyl acetate, methylpropionate, ethylpropionate, decanolide, mevalonolactone, caprolactone, etc. The above ether-based solvents may include dibutyl ether, tetraglame, deglame, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, etc. In addition, cyclohexanone, etc. may be used as the ketone-based solvent. In addition, ethyl alcohol, isopropyl alcohol, etc. may be used as the alcohol-based solvent, and as the aprotic solvent, nitriles such as R-CN (where R is a hydrocarbon group with a straight, branched, or ring structure having 2 to 20 carbon atoms and may include a double bond, a ring, or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, sulfolanes, etc. may be used.
[0143] The above organic solvents may be used alone or in a mixture of one or more. When used in a mixture of one or more, the mixing ratio can be appropriately adjusted according to the desired battery performance, which is widely understood by those engaged in the relevant field.
[0144] In addition, for the above carbonate-based solvent, it is preferable to use a mixture of cyclic carbonate and chain carbonate. In this case, using a mixture of cyclic carbonate and chain carbonate in a volume ratio of 1:1 to 1:9 can result in excellent performance of the electrolyte.
[0145] The above organic solvent may further include an aromatic hydrocarbon organic solvent in the carbonate-based solvent. In this case, the carbonate-based solvent and the aromatic hydrocarbon organic solvent may be mixed in a volume ratio of 1:1 to 30:1.
[0146] As the above aromatic hydrocarbon organic solvent, an aromatic hydrocarbon compound of the following chemical formula 6 may be used.
[0147] [Chemical Formula 6]
[0148]
[0149] (In the above chemical formula 6, R 30 to R 35 (These are identical or different from one another and are selected from the group consisting of hydrogen, halogens, alkyl groups having 1 to 10 carbon atoms, haloalkyl groups, and combinations thereof.)
[0150] Specific examples of the above aromatic hydrocarbon-based organic solvents include benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, fluorotoluene, 2,3-difluorotoluene, 2,4-difluorotoluene. It is selected from the group consisting of 2,5-difluorotoluene, 2,3,4-trifluorotoluene, 2,3,5-trifluorotoluene, chlorotoluene, 2,3-dichlorotoluene, 2,4-dichlorotoluene, 2,5-dichlorotoluene, 2,3,4-trichlorotoluene, 2,3,5-trichlorotoluene, iodotoluene, 2,3-diiodotoluene, 2,4-diiodotoluene, 2,5-diiodotoluene, 2,3,4-triiodotoluene, 2,3,5-triiodotoluene, xylene, and combinations thereof.
[0151] The above electrolyte may further include vinylene carbonate or an ethylene carbonate-based compound of the following chemical formula 7 as a life-enhancing additive to improve battery life.
[0152] [Chemical Formula 7]
[0153]
[0154] (In the above chemical formula 7, R 36 and R 37 The groups are identical or different from each other and are selected from the group consisting of hydrogen, halogen groups, cyano groups (CN), nitro groups (NO2), and fluorinated alkyl groups having 1 to 5 carbon atoms, and the R 36 and R 37At least one of the groups is selected from the group consisting of a halogen group, a cyano group (CN), a nitro group (NO2), and a fluorinated alkyl group having 1 to 5 carbon atoms, provided that R 36 and R 37 Not all of these are hydrogen.)
[0155] Representative examples of the above-mentioned ethylene carbonate-based compounds include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, or fluoroethylene carbonate. When using more of these lifespan-enhancing additives, the amount used can be appropriately controlled.
[0156] The above lithium salt is a material that dissolves in an organic solvent and acts as a source of lithium ions within the battery, enabling the basic operation of a lithium secondary battery and facilitating the movement of lithium ions between the anode and cathode. Representative examples of such lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide (LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, and LiN(C x F 2x+1 SO2)(C y F 2y+1The electrolyte comprises one or more supporting electrolytes selected from the group consisting of SO2)(where x and y are natural numbers, for example, integers from 1 to 20), lithium difluoro(bisoxolato) phosphate, LiCl, LiI, LiB(C2O4)2 (lithium bis(oxalato) borate (LiBOB), and lithium difluoro(oxalato) borate (LiDFOB). The concentration of the lithium salt is preferably used within the range of 0.1 M to 2.0 M. When the concentration of the lithium salt falls within the above range, the electrolyte has appropriate conductivity and viscosity, so it can exhibit excellent electrolyte performance and allow lithium ions to move effectively.
[0157] Depending on the type of lithium secondary battery, a separator may be present between the positive and negative electrodes. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or multilayer films of two or more layers thereof may be used, and of course, mixed multilayer films such as polyethylene / polypropylene two-layer separators, polyethylene / polypropylene / polyethylene three-layer separators, and polypropylene / polyethylene / polypropylene three-layer separators may be used.
[0158] FIG. 1 shows an exploded perspective view of a lithium secondary battery according to one embodiment of the present invention. Although the lithium secondary battery according to one embodiment is described as being prismatic, the present invention is not limited thereto and can be applied to various types of batteries such as cylindrical and pouch types.
[0159] Referring to FIG. 1, a lithium secondary battery (100) according to one embodiment may include an electrode assembly (40) wound with a separator (30) interposed between a positive electrode (10) and a negative electrode (20), and a case (50) in which the electrode assembly (40) is housed. The positive electrode (10), the negative electrode (20), and the separator (30) may be impregnated with an electrolyte (not shown).
[0160] Examples and comparative examples of the present invention are described below. However, the following examples are merely one example of the present invention, and the present invention is not limited to the following examples.
[0161] (Example 1)
[0162] A negative electrode active material slurry was prepared by mixing 96.9 wt% of a negative electrode active material (95:5 weight ratio) of a mixture of artificial graphite and a Si-carbon composite, 0.1 wt% of a room temperature molten salt of N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium tetrafluoroborate (DEMEBF4), and 3 wt% of a polyvinyl alcohol (PVA) binder in a water solvent. The Si-carbon composite comprises silicon and artificial graphite, wherein the weight ratio of Si is 50 wt% and the Si content in the total slurry is 2.5 wt%.
[0163] The above cathode active material slurry was applied to both sides of a copper foil current collector, and drying and rolling were performed to form a cathode active material layer with a cross-sectional thickness of 100 μm and a bulk density of 1.65 g / cm³, thereby manufacturing a cathode.
[0164] A positive electrode active material slurry was prepared by mixing 94 wt% of LiCoO2 positive electrode active material, 3 wt% of polyvinylidene fluoride binder, and 3 wt% of Ketjen black conductive material in an N-methylpyrrolidone solvent. The positive electrode active material slurry was applied to both sides of an Al foil current collector, and a positive electrode active material layer was formed by drying and rolling to manufacture a positive electrode.
[0165] A lithium secondary battery was manufactured by a conventional method using the above-described cathode, anode, and electrolyte. As the electrolyte, ethylene carbonate, ethylmethyl carbonate, and dimethyl carbonate (30:50:20 volume ratio) dissolved in 1.5M LiPF6 were used.
[0166] (Examples 2 to 9)
[0167] A cathode was prepared in the same manner as in Example 1 above, except that the room temperature molten salt content, room temperature molten salt type, binder type and binder content, and cathode active material content were changed as shown in Table 1 below. As the room temperature molten salt content changed, the anode active material content
[0168] A lithium secondary battery was manufactured using the above cathode, the anode of Example 1, and the electrolyte.
[0169] (Comparative Examples 1 to 9)
[0170] A cathode was prepared in the same manner as in Example 1 above, except that the room temperature molten salt content, room temperature molten salt type, binder type and binder content, and cathode active material content were changed as shown in Table 1 below.
[0171] A lithium secondary battery was manufactured using the above cathode, the anode of Example 1, and the electrolyte.
[0172] (Examples 10 to 14)
[0173] A cathode was manufactured in the same manner as Example 2 above, except that the cathode active material layer was manufactured so that the cross-sectional thickness and volume density were obtained as shown in Table 2 below.
[0174] A lithium secondary battery was manufactured using the above cathode, the anode of Example 1, and the electrolyte.
[0175] (Comparative Examples 10 to 14)
[0176] A cathode was manufactured in the same manner as in Example 1 above, except that a room temperature molten salt was not used, and the cathode active material layer was manufactured such that the cross-sectional thickness and bulk density were obtained as shown in Table 2 below.
[0177] A lithium secondary battery was manufactured using the above cathode, the anode of Example 1, and the electrolyte.
[0178] (Comparative Example 15)
[0179] A negative electrode active material slurry was prepared by mixing 97 wt% of a mixture of artificial graphite and Si (95:5 weight ratio) and 3 wt% of a polyvinyl alcohol binder in a water solvent.
[0180] The above cathode active material slurry was applied to both sides of a copper foil current collector, and drying and rolling were performed to form a cathode active material layer with a cross-sectional thickness of 100 μm and a bulk density of 1.65 g / cm³, thereby manufacturing a cathode.
[0181] An electrolyte was prepared by adding room temperature molten salt of DEMEBF4 to a mixture of ethylene carbonate, ethylmethyl carbonate, and dimethyl carbonate (30:50:20 volume ratio) in which 1.5M LiPF6 was dissolved.
[0182] At this time, the content of the above-mentioned room temperature molten salt was used at 0.5% by weight relative to 100% by weight of the total electrolyte.
[0183] A lithium secondary battery was manufactured using the above cathode, the above electrolyte, and the above anode of Example 1.
[0184] (Example 15)
[0185] A negative electrode active material slurry was prepared by mixing 96.7 wt% of a mixture of artificial graphite and Si (95:5 weight ratio) negative electrode active material, 0.3 wt% of a room temperature molten salt of DEMEBF4, and 3 wt% of a polyvinyl alcohol binder in a water solvent.
[0186] The above cathode active material slurry was applied to both sides of a copper foil current collector, and drying and rolling were performed to form a cathode active material layer with a cross-sectional thickness of 100 μm and a bulk density of 1.65 g / cm³, thereby manufacturing a cathode.
[0187] A lithium secondary battery was manufactured using the above cathode, the anode of Example 1, and the electrolyte.
[0188] (Example 16)
[0189] An electrode was manufactured in the same manner as in Example 15 above, except that a mixture of artificial graphite and Si (90:10 weight ratio) was used as the negative electrode active material.
[0190] A lithium secondary battery was manufactured using the above cathode, the anode of Example 1, and the electrolyte.
[0191] (Comparative Example 16)
[0192] A negative electrode active material slurry was prepared by mixing 97 wt% of a mixture of artificial graphite and Si (95:5 weight ratio) and 3 wt% of a polyvinyl alcohol binder in a water solvent, and a negative electrode was prepared in the same manner as in Example 16 using this negative electrode active material slurry.
[0193] A lithium secondary battery was manufactured using the above cathode, the anode of Example 1, and the electrolyte.
[0194] (Comparative Example 17)
[0195] A negative electrode active material slurry was prepared by mixing 97 wt% of a mixture of artificial graphite and Si (90:10 weight ratio) and 3 wt% of a polyvinyl alcohol binder in a water solvent, and a negative electrode was prepared in the same manner as in Example 17 using this negative electrode active material slurry.
[0196] A lithium secondary battery was manufactured using the above cathode, the anode of Example 1, and the electrolyte.
[0197] (Comparative Example 18)
[0198] A negative electrode active material slurry was prepared by mixing 96.7 wt% of artificial graphite negative electrode active material, 0.3 wt% of room temperature molten salt, and 3 wt% of polyvinyl alcohol binder in a water solvent, and a negative electrode was prepared in the same manner as in Example 16 using this negative electrode active material slurry.
[0199] A lithium secondary battery was manufactured using the above cathode, the anode of Example 1, and the electrolyte.
[0200] (Comparative Example 19)
[0201] A cathode active material slurry was prepared by mixing 97 wt% of artificial graphite cathode active material and 3 wt% of polyvinyl alcohol binder in a water solvent, and a cathode was prepared in the same manner as Comparative Example 14 using this cathode active material slurry.
[0202] A lithium secondary battery was manufactured using the above cathode, the anode of Example 1, and the electrolyte.
[0203] (Comparative Example 20)
[0204] A negative electrode active material slurry was prepared by mixing 97 wt% of Si negative electrode active material and 3 wt% of polyvinyl alcohol binder in a water solvent.
[0205] The above cathode active material slurry was applied to both sides of a copper foil current collector, and drying and rolling were performed to form a cathode active material layer with a cross-sectional thickness of 100 μm and a bulk density of 1.65 g / cm³, thereby manufacturing a cathode.
[0206] A positive electrode active material slurry was prepared by mixing 93.9 wt% of LiCoO2 positive electrode active material, 0.1 wt% of DEMEBF4 room temperature molten salt, 3 wt% of polyvinyl alcohol binder, and 3 wt% of Ketjen black conductive material in a water solvent. The positive electrode active material slurry was applied to both sides of an Al foil current collector, and a positive electrode active material layer was formed by drying and rolling to manufacture a positive electrode.
[0207] A lithium secondary battery was manufactured by a conventional method using the above-described cathode, anode, and electrolyte. As for the electrolyte, ethylene carbonate, ethylmethyl carbonate, and dimethyl carbonate (30:50:20 volume ratio) dissolved in 1.5M LiPF6 were used.
[0208] (Comparative Example 21)
[0209] A cathode active material slurry was prepared by mixing 93.9 wt% of LiCoO2 cathode active material, 0.1 wt% of DEMEBF4 room temperature molten salt, 3 wt% of polyvinylidene fluoride binder, and 3 wt% of Ketjen black conductive material in an N-methylpyrrolidone solvent. A cathode was prepared in the same manner as Comparative Example 12.
[0210] A lithium secondary battery was manufactured by a conventional method using the anode, the cathode of Comparative Example 12, and the electrolyte.
[0211] (Comparative Example 22)
[0212] A cathode was prepared in the same manner as Comparative Example 12, except that a cathode active material slurry prepared by mixing 94 wt% of LiCoO2 cathode active material, 3 wt% of polyvinyl alcohol binder, and 3 wt% of Ketjen black conductive material in a water solvent was used.
[0213] A lithium secondary battery was manufactured by a conventional method using the anode, the cathode of Comparative Example 12, and the electrolyte.
[0214] (Comparative Example 23)
[0215] A cathode was prepared in the same manner as Comparative Example 13, except that a cathode active material slurry prepared by mixing 94 wt% of LiCoO2 cathode active material, 3 wt% of polyvinylidene fluoride binder, and 3 wt% of Ketjen black conductive material in an N-methylpyrrolidone solvent was used.
[0216] A lithium secondary battery was manufactured by a conventional method using the anode, the cathode of Comparative Example 13, and the electrolyte.
[0217] Experimental Example 1) Crack Evaluation
[0218] Crack formation was evaluated by visually observing the cathode surfaces prepared according to Examples 1 to 16 and Comparative Examples 1 to 23.
[0219] Among the results, the results of Examples 1 to 9 and Comparative Examples 1 to 9 are shown in Table 1 below, and the results of Examples 10 to 14 and Comparative Examples 10 to 14 are shown in Table 2 below. In addition, the results of Comparative Example 15 are shown in Table 3 below, and for comparison, the results of Example 1 and Comparative Example 1 are also shown together in Table 3 below. Furthermore, the results of Examples 15 and 16 and Comparative Examples 16 to 19 are shown in Table 4 below, and the results of Comparative Examples 20 to 23 are shown in Table 5 below.
[0220] Experimental Example 2) Evaluation of Dose Retention Rate
[0221] The lithium secondary batteries prepared according to Examples 1 to 16 and Comparative Examples 1 to 23 were subjected to 100 charge-discharge cycles at 1 C. The ratio of the 100-cycle discharge capacity to the 1-cycle discharge capacity was calculated.
[0222] Among the results, the results of Examples 1 to 9 and Comparative Examples 1 to 9 are shown in Table 1 below, and the results of Examples 10 to 14 and Comparative Examples 10 to 14 are shown in Table 2 below. In addition, the results of Comparative Example 15 are shown in Table 3 below, and for comparison, the results of Example 1 and Comparative Example 1 are also shown together in Table 3 below. Furthermore, the results of Examples 15 and 16 and Comparative Examples 16 to 19 are shown in Table 4 below, and the results of Comparative Examples 20 to 23 are shown in Table 5 below.
[0223] Experimental Example 3) Measurement of Energy Density
[0224] A half-cell was prepared using the negative electrode, lithium metal counter electrode, and electrolyte prepared according to Examples 15 and 16 and Comparative Examples 16 to 19. As the electrolyte, ethylene carbonate, ethylmethyl carbonate, and dimethyl carbonate (30:50:20 volume ratio) in which 1.5 M LiPF6 was dissolved were used.
[0225] The above half-cell was charged and discharged once at 0.2C, and the capacity per weight of the active material was calculated and used as the energy density. For Comparative Example 16, in which artificial graphite and Si were mixed in a weight ratio of 95:5 as the negative electrode active material, the ratio of the measured energy densities was calculated, and the results are shown in Table 4 below.
[0226] In the table below,
[0227] DEMEBF4: N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium tetrafluoroborate
[0228] EMIBF4: 1-ethyl-3-methylimidazolium tetrafluoroborate
[0229] DEMETFSI: N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethylsulfonyl)imide
[0230] PP13TFSI: N-methyl-N-propylpiperidinium bis(trifluoromethylsulfonyl)imide
[0231] PVA: Polyvinyl alcohol
[0232] PAA: Polyacrylic acid
[0233] SBR: Styrene-butadiene rubber
[0234] CMC: Carboxymethylcellulose
[0235] PVdF: Polyvinylidene Fluoride
[0236] Room temperature molten salt content (weight%) Room temperature molten salt bookbinder Binder content (weight%) Cathode active material content (weight%) cathode active material layer Discharge Capacity Retention Rate (%) One side thickness (㎛) Bulk density (g / cm³) crack Example 1 0.1 DEMEBF4 PVA 3 96.9 100 1.65 radish 87 Example 2 0.5 DEMEBF4 PVA 3 96.5 100 1.65 radish 92 Example 3 0.5 EMIBF4 PVA 3 96.5 100 1.65 radish 81 Example 4 0.5 DEMETFSI PVA 3 96.5 100 1.65 radish 70 Example 5 0.5 PP13TFSI PVA 3 96.5 100 1.65 radish 72 Example 6 0.5 DEMEBF4 PVA 3 96.5 100 1.65 radish 90 Example 7 0.5 DEMEBF4 PVA / PAA (50:50 weight ratio) 3 96.5 100 1.65 radish 92 Example 8 1.0 DEMEBF4 PVA 3 96 100 1.65 radish 90 Example 9 5.0 DEMEBF4 PVA 3 92 100 1.65 radish 83 Comparative Example 1 0 - PVA 3 97 100 1.65 you 51 Comparative Example 2 0 - PVA 3 97 100 1.65 you 45 Comparative Example 3 0 - PVA / PAA (50:50 weight ratio) 3 97 100 1.65 you 52 Comparative Example 4 0.5 DEMEBF4 SBR / CMC (33:67 weight ratio) 3 96.5 100 1.65 radish 24 Comparative Example 5 0 - SBR / CMC (33:67 weight ratio) 3 97 100 1.65 radish 23 Comparative Example 6 0.5 DEMEBF4 PVdF 3 96.5 100 1.65 radish 23 Comparative Example 7 0 - PVdF 3 97 100 1.65 radish 21 Comparative Example 8 0.5 DEMEBF4 PAN 3 96.5 100 1.65 radish 32 Comparative Example 9 0 - PAN 3 100 1.65 you 32
[0237] As shown in Table 1 above, in the case of Examples 1 to 9, in which a volume expansion-reducing binder and a room-temperature molten salt were used with a silicon-based active material, it can be seen that no cracks occurred during electrode manufacturing and an excellent capacity retention rate was exhibited. This appears to be because the inclusion of the room-temperature molten salt in the negative electrode active material layer caused softening of the electrode, thereby preventing cracks from occurring during electrode manufacturing. Furthermore, since the volume expansion-reducing binder within the negative electrode active material layer has high ionic conductivity, it is believed that even if the ion conduction pathway of the silicon-based negative electrode active material is blocked due to volume expansion during cycling, an excellent capacity retention rate is exhibited due to the high ionic conductivity of the binder.
[0238] On the other hand, in the case of Comparative Examples 1 to 3, which did not use room temperature molten salt even when a volume expansion-reducing binder was used, cracks occurred during electrode manufacturing and a significantly low capacity retention rate was observed. This appears to be because the discharge capacity was reduced due to the precipitation of lithium metal on the cathode during cycling, caused by the low impregnation of the electrolyte and the blockage of the ion conduction path after expansion and shrinkage.
[0239] In addition, in the case of Comparative Examples 4 to 9, in which a volume expansion reducing binder was not used, the volume expansion of silicon was not suppressed, and the binder and the room temperature molten salt were not combined, resulting in the side effect of the room temperature molten salt being reduced and decomposed at the graphite edge, and it can be seen that the capacity retention rate decreased rapidly.
[0240] Room temperature molten salt content (weight%) Room temperature molten salt bookbinder Binder content (weight%) Cathode active material content (weight%) cathode active material layer Discharge Capacity Retention Rate (%) One side thickness (㎛) Bulk density (g / cm³) crack Example 10 0.5 DEMEBF4 PVA 3 96.5 72 1.65 radish 95 Example 11 0.5 DEMEBF4 PVA 3 96.5 90 1.65 radish 92 Example 12 0.5 DEMEBF4 PVA 3 96.5 100 1.60 radish 91 Example 13 0.5 DEMEBF4 PVA 3 96.5 100 1.7 radish 88 Example 14 0.5 DEMEBF4 PVA 3 96.5 110 1.65 radish 82 Comparative Example 10 0 - PVA 3 97 72 1.65 radish 86 Comparative Example 11 0 - PVA 3 97 90 1.65 you 62 Comparative Example 12 0 - PVA 3 97 100 1.60 you 55 Comparative Example 13 0 - PVA 3 97 100 1.70 you 49 Comparative Example 14 0 - PVA 3 97 110 1.65 you 46
[0241] As shown in Table 2 above, in the case of Examples 10 to 14, which use a room temperature molten salt and a volume expansion reducing binder together, it can be seen that even when the thickness and volume density of the negative electrode active material layer are increased, no cracks occur and an excellent capacity retention rate is exhibited. On the other hand, in the case of Comparative Examples 10 to 14, which do not use a room temperature molten salt even when a volume expansion reducing binder is used, it can be seen that when the thickness and volume density of the negative electrode active material layer are increased, cracks occur and the capacity retention rate deteriorates significantly.
[0242] Room temperature molten salt content (weight%) Room temperature molten salt Room temperature molten salt addition method cathode active material layer Discharge Capacity Retention Rate (%) One side thickness (㎛) crack Example 1 0.5 DEMEBF4 cathodic addition 100 radish 87 Comparative Example 15 0.5 DEMEBF4 Electrolyte addition 100 you 45 Comparative Example 1 0 - No additives 100 you 51
[0243] As shown in Table 3 above, it can be seen that when room temperature molten salt is added to the electrolyte, the effects of suppressing crack formation and improving capacity retention rate cannot be obtained. In particular, it can be seen that the room temperature molten salt lowers the ionic conductivity of the electrolyte and undergoes reductive decomposition on the surface of the negative electrode active material, thereby worsening the capacity retention rate.
[0244] Room temperature molten salt content (weight%) Room temperature molten salt Active material (weight ratio) bookbinder Binder content (weight%) Cathode active material content (weight%) cathode active material layer Discharge Capacity Retention Rate (%) Energy density ratio (%) crack Example 15 0.3 DEMEBF4 Graphite / Si(95 / 5) PVA 3 100 radish 90 Example 16 0.3 DEMEBF4 Graphite / Si(90 / 10 PVA 3 113 radish 81 Comparative Example 16 0 - Graphite / Si(95 / 5) PVA 3 100 you 51 Comparative Example 17 0 - Graphite / Si(90 / 10) PVA 3 113 you 39 Comparative Example 18 0.3 DEMEBF4 Graphite / Si(100 / 0 PVA 3 86.6 radish 93 Comparative Example 19 0 - Graphite / Si(100 / 0) PVA 3 86.6 you 92
[0245] As shown in Table 4 above, even when graphite is mixed and used as the negative electrode active material, when a silicon-based negative electrode active material is used, it can be seen that crack prevention and excellent capacity retention results can be obtained by using a room temperature molten salt and a volume expansion reduction binder.
[0246] On the other hand, it can be seen that when only artificial graphite is used without silicon-based active materials, there is no effect in improving capacity retention rate. Furthermore, it can be seen that energy density decreases when silicon-based active materials are not used.
[0247] From these results, it can be seen that in order to obtain excellent energy density and discharge capacity retention rate, silicon-based active materials must be used as the negative electrode active material, and volume expansion reduction binders and room-temperature molten salts must be used.
[0248] Room temperature molten salt content (weight%) Room temperature molten salt bookbinder Binder content (weight%) Cathode active material content (weight%) positive active material layer Discharge Capacity Retention Rate (%) crack Comparative Example 20 0.1 DEMEBF4 PVA 3 96.9 radish 49 Comparative Example 21 0.1 DEMEBF4 PVdF 3 96.9 radish 53 Comparative Example 22 0 - PVA 3 97 you 46 Comparative Example 23 0 - PVdF 3 97 you 51
[0249] As shown in Table 5 above, it can be seen that even when room temperature molten salt and volume expansion reducing binder are used together, when they are used as a positive electrode and silicon-based negative electrode active material is used, the effect of improving capacity retention rate is minimal.
[0250] Although preferred embodiments of the present invention have been described above, the present invention is not limited thereto and can be implemented with various modifications within the scope of the claims, the detailed description of the invention, and the attached drawings, and it is obvious that such modifications also fall within the scope of the present invention.
Claims
Claim 1 A negative electrode for a lithium secondary battery comprising: a current collector; and a negative electrode active material layer located on the current collector, wherein the negative electrode active material layer comprises a silicon-based negative electrode active material, a room temperature molten salt, and a volume expansion reducing binder, wherein the silicon-based negative electrode active material is a Si-carbon composite comprising silicon and crystalline carbon or Si, and the volume expansion reducing binder is polyvinyl alcohol, polyacrylic acid, or a combination thereof. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 A negative electrode for a lithium secondary battery according to claim 1, wherein the room temperature molten salt comprises a cation which is any one of the cations represented by the following chemical formulas 1 to 5. [Chemical Formula 1] (In the above chemical formula 1, R 1 , R 2 , R 3 and R 4 ) are identical or different from each other and are hydrogen, unsubstituted or substituted aliphatic groups, aromatic groups, heterocyclic groups, or unsubstituted or substituted alkoxy groups) [Chemical Formula 2] (In the above chemical formula 2, R 5 is an alkyl group of hydrogen atoms or carbon atoms 1-5, and R 6 , R 7 , R 8 ☐ and ☐ are identical or different from each other, and are hydrogen, a C1-5 alkyl group, an alkoxy group, an amino group, or a nitro group, and m is 4 or 5.)[Chemical Formula 3] (In the above chemical formula 3, R 9 is an alkyl group of hydrogen atoms or carbon atoms 1-5, and R 10 , R 11 , R 12 ☐ and ☐ are identical or different from each other, and are hydrogen, a C1-5 alkyl group, an alkoxy group, an amino group, or a nitro group, and m1 is an integer from 4 to 5)[Chemical Formula 4] (In the above chemical formula 4, R 13 is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and R 14 , R 15 , R 16 are identical or different from each other, and are hydrogen, a C1-5 alkyl group, an alkoxy group, an amino group, or a nitro group, and R 17 is an alkyl group having 1 to 5 carbon atoms, m2 is an integer from 0 to 2, and m+n is 3 or 4.[Chemical Formula 5] (In the above chemical formula 5, R 18 is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and R 19 , R 20 , R 21 are identical or different from each other, and are hydrogen, a C1-5 alkyl group, an alkoxy group, an amino group, or a nitro group, and R 22 is an alkyl group having 1 to 5 carbon atoms, m2 is an integer from 0 to 2, and m+n is 3 or 4.) Claim 6 A negative electrode for a lithium secondary battery according to claim 5, wherein the cation is an alkyl quaternary ammonium cation, an N-methyl-N-propylpiperidinium cation, or an N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium cation. Claim 7 A negative electrode for a lithium secondary battery according to claim 1, wherein the room temperature molten salt comprises an anion having a fluorine atom. Claim 8 In claim 7, the anion having the fluorine atom is BF4 - , PF6 - , C n F 2n+1 CO2 - (n is an integer from 1 to 4), C m F 2m+1 SO3 - (m is an integer from 1 to 4), (FSO2)2N - , (CF3SO2)2N - , (C2F5SO2)2N - , (CF3SO2)(C4F9SO2)N - , (CF3SO2)3C - , CF3SO2-N - -COCF3 or R a -SO2-N - -SO2CF3(R a A negative electrode for a lithium secondary battery in which represents an aliphatic or aromatic group. Claim 9 A negative electrode for a lithium secondary battery according to claim 1, wherein the content of the room temperature molten salt is 0.1% to 5% by weight with respect to 100% by weight of the entire negative electrode active material layer. Claim 10 A negative electrode for a lithium secondary battery according to claim 1, wherein the content of the volume expansion reducing binder is 2% to 6% by weight with respect to 100% by weight of the entire negative electrode active material layer. Claim 11 A negative electrode for a lithium secondary battery according to claim 1, wherein the weight ratio of the room temperature molten salt to the volume expansion reducing binder is 0.3 to 1:
3. Claim 12 delete Claim 13 A lithium secondary battery comprising a negative electrode according to any one of claims 1 and 5 to 11; a positive electrode; and an electrolyte.
Citation Information
Patent Citations
Negative electrode material for non-aqueous electrolyte secondary battery, negative electrode for non-aqueous electrolyte secondary battery, production method therefor, and non-aqueous electrolyte secondary battery
KR1020160118258A
Binder for non-aqueous electrolye rechargeable battery, negative electrode slurry for rechargeable battery including the same, negative electrode for rechargeable battery including the same and rechargeable battery including the same
KR1020200125503A
Negative electrode for secondary batteries, secondary battery, battery pack, electric vehicle, energy storage system, electric tool and electronic device
WO2019022044A1
